The Role of Some Medicinal Plants in the Management of Peptic Ulcer - Al-Jawad, Faruk H.; Ismael, Ahmed H.; Nile, Anees K.; Sahib, Ahmed S. (AL-Kindy College Medical Journal, 2011)
Background: Plants used in folk medicine for the treatment of peptic ulcer diseases is a very promising approach to overcome the limitations of classical medicines. Aim: To explore the efficacy of medicinal plants, namely turmeric, garlic and marshmallow, in eradication of H. pylori. Methods: This prospective study was carried out on 225 of well-known dyspeptic patients who were divided into four groups; a control group (received classical medical therapy) and three other groups that received one of the three medicinal plants, plus the same therapy used in the control group. The follow up was done by using a questionnaire form, endoscopic examination, and determination of serum levels of anti H.pylori antibodies & gastrin by using ELISA test. In addition, liver enzymes were monitored by using spectrophotometer to prove the safety of medicinal plants. Results: The rate of recurrence of peptic ulcer disease was decreased in patients who received the combined therapy when compared to the patients in control group. Medicinal plants were effective in decreasing the recurrence of H. pylori infection when each one of them was used in combination with the medical therapy without causing harmful effects on the liver. Conclusion: Turmeric, garlic & marshmallow are effective in management of peptic ulcer with low cost.